Last term at malory towers - Blyton, Enid (Mammoth London, 2000)
Darrell's last term at Malory Towers promises to be as exciting as ever. There's a new girl, Amanda, a stubborn sports star set on swimming in the dangerous sea - with or without permission. And there's spoilt Jo who's only happy when she gets her own way.